Pembuatan Aplikasi Mobile Learning sebagai Sarana Pembelajaran di Lingkungan Universitas Diponegoro - Afandi Nur Aziz Thohari; Kodrat Iman Satoto; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2013)
Mobile learning is the intersection of Mobile Computing and E-Learning that provides the resources that can be accessed from anywhere, a powerful search system capabilities, rich interaction, full support for effective learning and assessment based on performance. E-learning has the characteristics are independent of place and time. Education requires an alternative model of learning has not characteristic depending on location and time. In addition to the proficiency level, an alternative model is also expected to provide knowledge sharing and visualization facilities of knowledge so that knowledge becomes more interesting and easy to understand. Mobile learning application built to run on android operating system. Android operating system was chosen because it has mastered the current android smartphone market and is an open source operating system that is easy to develop. Android versions that support this application is version 2.2 to 4.2. Using jQuery mobile framework allows users to access the M-Learning. Because besides its attractive, jQuery mobile display can also customize the display of the mobile device.